2002
DOI: 10.1111/j.1749-6632.2002.tb02919.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a Component of Wine and Grapes, in the Prevention of Kidney Disease

Abstract: Ischemia is an inciting factor in 50% of incidences of acute renal failure, and it increases the risk of organ rejection after renal transplantation. We have previously demonstrated that resveratrol (RSV) reduces ischemia-reperfusion (I/R) injury of rat kidney both by antioxidant and anti-inflammatory mechanisms. However, a clear morphological demonstration of this activity has not been made. To answer this question we have performed a new set of experiments following the experimental protocol reported below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
(24 reference statements)
0
39
1
1
Order By: Relevance
“…In previous studies, it has been established that black grape and tomato have high antioxidant contents (Alcolea et al, 2002;Bertelli et al, 2002;Weisburger, 2002) and can make a contribution to the antioxidant power in vivo (Ozturk et al, 1999;Visioli et al, 2003). However, results of the present study demonstrate that dried black grape can provide significant protection against cisplatininduced peroxidation reactions; tomato juice does also, but to a lesser extent.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In previous studies, it has been established that black grape and tomato have high antioxidant contents (Alcolea et al, 2002;Bertelli et al, 2002;Weisburger, 2002) and can make a contribution to the antioxidant power in vivo (Ozturk et al, 1999;Visioli et al, 2003). However, results of the present study demonstrate that dried black grape can provide significant protection against cisplatininduced peroxidation reactions; tomato juice does also, but to a lesser extent.…”
Section: Discussioncontrasting
confidence: 76%
“…In previous studies, it has been established that dried black grape may strengthen the antioxidant potential of the body and thus reduce some oxidant stress-induced health problems (Ozturk et al, 1999;Bertelli et al, 2002). Similarly, it has been established in the previous studies that tomato also has antioxidant power due to its rich lycopene content (Stahl and Sies, 1996), and that its use may be helpful for the amelioration of some oxidant stress-related diseases (Agarwall and Rao, 2000).…”
Section: Introductionmentioning
confidence: 88%
“…Several studies have examined the effects of resveratrol on peripheral organ systems and have reported that resveratrol can provide protection to the heart (8, 53) and kidney (7,43,52) and may inhibit carcinogenesis (24,34). In addition, others have reported that resveratrol may play a beneficial role in impaired vascular function of large peripheral blood vessels during type 1 (41,44) and type 2 (57) diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been reported to have a variety of pharmacological effects, including anti-inflammatory, anticarcinogenic, antioxidant, and antiplatelet properties (5,6,20,24,45,55,58). Several investigators have shown that resveratrol has both acute and chronic influences on organ systems (7,8,45,53) and endothelial function of large peripheral blood vessels during T1D (41, 44). The mechanisms that account for the effects of resveratrol on vascular function are varied but appear to involve an increase in the expression of eNOS, an increase in the expression of antioxidant pathways and pathways that might regulate antioxidant responses in cells (including SIRT1 and Nrf2), and/or a decrease in the expression of endothelin (13,22,41,44,47,53,58).…”
mentioning
confidence: 99%
“…In previous work, red wine polyphenol resveratrol caused an attenuation of oxidative damage and decreased vulnerability of the kidney to ischaemiareperfusion damage [7,8]. Nevertheless, it is not well established whether this protection is mechanistically linked to the reported effects of the various wine components since these effects have not been separately studied.…”
Section: Introductionmentioning
confidence: 99%